Cellular heterogeneity identified by single-cell alkaline phosphatase (ALP) via a SERRS-microfluidic droplet platform. Issue 2 (19th December 2018) - Sun, Dan; Cao, Fanghao; Cong, Lili; Xu, Weiqing; Chen, Qidan; Shi, Wei; Xu, Shuping
Abstract : We proposed an ultrasensitive method for studying low abundance ALP secreted by individual cell using the microfluidic droplet-based SERRS technique. Abstract : Alkaline phosphatase (ALP) is a useful indicator for disease state diagnosis and clinical outcome. Investigation of ALP expression among cells is still challenging since ALP expression in a single cell is too low to be detectable. In our work, an ultrasensitive, high-throughput analytical method was applied for ALP determination in a single cell by using a surface-enhanced resonance Raman scattering (SERRS)-based microfluidic droplet technique. An ALP catalyzed substrate (5-bromo-4-chloro-3-indolyl phosphate, BCIP) was used to evaluate ALP activity in the cell within one droplet. When BCIP was incubated with cells, ALP can catalyze a hydrolysis reaction of colorless BCIP and oxidize the intermediate compound to form blue 5, 5′-dibromo-4, 4′-dichloro-1 H, 1 H -[2, 2′]biindolylidene-3, 3′-dione (BCI), which is a resonant Raman-active species. The encapsulation of BCI in droplets is favorable for detecting extremely low levels of molecules due to an accumulation effect along with reaction time. The ALP concentration as low as 1.0 × 10 −15 M can be successfully detected in a uniform droplet. In addition, cellular heterogeneity profiled by ALP expression on single-cell resolution was monitored with this SERRS-based microfluidic droplet technique. Ultrasensitive determination of ALP secreted from individual cells can help us to understand cell-to-cell heterogeneity.